Prevention of Musculoskeletal Disorder (MSDs) at Kakimoto House Japan Lumber Mill Using the Ovako Working Analysis System (OWAS) Method and Design of Work Facilities - Jip Rayhan Xavier Janaprasetya; Firman Ardiansyah Ekoanindiyo (JTI: Jurnal Teknik Industri, 2024)
The timber industry heavily relies on its workforce, making worker well-being and posture maintenance essential to prevent musculoskeletal disorders (MSDs) resulting from repetitive tasks, non-ergonomic environments, and constrained working conditions. MSDs significantly impact productivity and worker health, necessitating ergonomic interventions like the Ovako Work Analysis System (OWAS). This anthropometric method evaluates worker postures by categorizing body movements into intervals, focusing on the back, arms, and legs, and identifying postures that pose a high risk of injury. At Kakimoto House Japan, where manual material handling (MMH) is predominant, OWAS was applied to analyze and address workers' physical strain, ensuring comprehensive data collection through sufficiency testing. Data analysis using the 5th, 50th, and 95th percentiles provided valuable insights into posture distribution and workload impact. Implementing a new carriage design enabled workers to carry more wood with less effort, reducing physical strain and improving task efficiency. This ergonomic improvement highlights the potential for enhanced productivity and health outcomes in the timber industry.Keywords: Ergonomic, OWAS,MSDs